A Comparison of the flexural strength of self-cured and dual-cured alkasite restorative filling material an in vitro study - Arellano, Allen Vince S.; Datingaling, Ma. Patrcia; Ocampo, Paolo Vincent G.; Publico, Gian Carlo E.; Santiago, Dan Aron A. (Department of Community Dentistry, University of the Philippines Manila, 2018)
Introduction: Cention N is a new material developed by Ivoclar Vivadent which is said to have physical properties comparable to dental amalgam, an ion-releasing potential and is tooth-colored. It comes in powder and liquid and sets through self-cure with optional light-curing. The study aimed to determine the difference in the flexural strength of self-cured and dual-cured alkasite material.